A Simple and Rapid Method for Preparing a Cell-Free Bacterial Lysate for Protein Synthesis - Krinsky, Nitzan; Kaduri, Maya; Shainsky-Roitman, Janna; Goldfeder, Mor; Ivanir, Eran; Benhar, Itai; Shoham, Yuval; Schroeder, Avi (PLOS ONE, 2016)
Cell-free protein synthesis (CFPS) systems are important laboratory tools that are used for various synthetic biology applications. Here, we present a simple and inexpensive laboratory-scale method for preparing a CFPS system from E. coli. The procedure uses basic lab equipment, a minimal set of reagents, and requires less than one hour to process the bacterial cell mass into a functional S30-T7 extract. BL21(DE3) and MRE600 E. coli strains were used to prepare the S30-T7 extract. The CFPS system was used to produce a set of fluorescent and therapeutic proteins of different molecular weights (up to 66 kDa). This system was able to produce 40–150 μg-protein/ml, with variations depending on the plasmid type, expressed protein and E. coli strain. Interestingly, the BL21-based CFPS exhibited stability and increased activity at 40 and 45°C. To the best of our knowledge, this is the most rapid and affordable lab-scale protocol for preparing a cell-free protein synthesis system, with high thermal stability and efficacy in producing therapeutic proteins.